Relasi Seni, Teknologi dan Masyarakat - Bambang Sunarto (PROSIDING: SENI, TEKNOLOGI, DAN MASYARAKAT, 2022)
Abstract Art, technology, and society are three different entities. As distinct entities, they inevitably interact with one another. These interactions produce various types and benefits of technology. The method used in understanding the interaction of the three entities is to use the literature study method. This method generates an understanding of the types and benefits of technology and the function of using art in society. The results show an understanding that although the phenomenon of art technology is a fact that exists before our eyes, there are not many studies related to this problem. Therefore, art technology can be studied more deeply in descriptive and applied artistic disciplines.